Intercollegiate athletics vs. academics: The Student-Athlete or the Athlete-Student - Saffici, C.; Pellegrino, R. (The Sport Journal, 2012)
Athletic programs at many colleges and universities are inconsistent with the school`s mission statements. The term "student-athlete" basically means that they are students first, and then athletes. We have reached a point here it can be argued that they are instead more athlete-students.